Avaliação da superestrutura de pontes através de parâmetros dinâmicos - Braido, Jorge Dalmas (2014)
Bridges' inspections is a visual process only, which is strongly dependent of engineer s experience. It s a simple but incomplete method, because cannot identify changes in materials property. To solve this problem, it can use the structural monitoring, which does the bridge's inspection from the instrumentation of the structure. The stuctural behaviour is defined through samples and described from modal parameters like natural frequencies, modal shapes and damping factor. In comparison with a visual assessment more reliable results are shown because utilizes samples from the real behaviour of the structure. This is a quantitative research which has two different phases: numerical and experimental. In the experimental phase, it uses a accelerometer from a mobile phone to extract samples of the structure. Natural frequencies are determined by the use of the Fast Fourier Transform (FFT). In the numerical phase, it uses the finite element method (FEM) to represent the structure, then it s possible obtain natural frequencies and modal shapes attached to the real structure. The numerical model is calibrated until the answer shows a little difference to the real answer of the bridge. The metodology, at the end of the research, can identify the real and actual behaviour from bridges in a reliable and simple way, with low cost. The research is realized in two concrete bridges located at Passo Fundo/RS